The landscape of EdD programmes in England - Aldred, Elaine Mary (2018)
Professional Doctorates in Education (EdD) have been established in many universities in England over the last 25 years, but there is little empirical research on them. The studies that do exist are largely literature reviews comparing professional doctorates to traditional doctorates. The empirical work tends to be student-centred, dealing with issues such as motivation for undertaking a professional doctorate; how professional doctorates impact on professional identities; and, the type of critical skills required to engage successfully with a professional doctorate. There has been one empirical survey of EdDs, but this was only as part of a wider survey on the field of professional doctorates. What is missing is twofold: first a consideration of the landscape of EdD programmes; what is being offered where, and how might we understand the nature of the knowledge acquired. Secondly, there is no description of the pedagogical frameworks of EdDs and how these bridge the various knowledge boundaries between theoretical, academic and professional knowledges. This thesis sets out to investigate these issues. The study draws on the theoretical concepts of Basil Bernstein and, in part, Karl Maton’s development of these concepts. Maton’s extension of Bernstein’s horizontal and vertical discourse, the semantics modality of legitimation code theory, was used to situate the EdD programmes in relation to one another with regards to the type of knowledge transmitted and acquired by students engaged in those EdDs. This was done through a survey of the EdD websites, quantifying the discourse of those websites and relevant online documentation related to the programmes. Having mapped the programmes through this survey of publicly available material, three partial case studies were developed, each demonstrating a different knowledge focus and pedagogical approach. I used Bernstein’s concept of classification and framing to describe how the pedagogical process of the EdD might, or might not, weaken the boundaries between theoretical knowledge and professional knowledge thereby making it possible for students to connect the two. The findings showed that most EdD programmes emphasised context-independent knowledge and context-dependent knowledge in broadly equal measure. Diverse students were accommodated within structured curricula in communities of learners, albeit in slightly different ways, by providing a theoretical and pedagogical framework in which the students found commonalities and by drawing on the shared experiences of different professional practices to enrich students’ learning experience. Despite each programme having a different focus, all programmes allowed students to develop their own research focus relevant to their professional practice. The deeper description of the three partial case studies also indicated that although the programme focus was an important part of enabling students to find an EdD which best suited their needs, the pedagogic framework should carry equal weight with regards to facilitating students’ ability to connect theoretical knowledge to professional knowledge. For this reason, the pedagogic approach should also be explicated clearly as part of the online information. There has not been any recent mapping of professional doctorates such as EdDs in England. This research has developed a new approach to this problem that a) sheds light on EdDs in England and b) could be useful in mapping other professional doctorates and investigating knowledge acquisition and production in these disciplines.